2022
DOI: 10.3390/s22072750
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Tillage Depth on the Working Performance of Tractor-Moldboard Plow System under Various Field Environments

Abstract: The purpose of this study was to analyze the tillage depth effect on the tractor-moldboard plow systems in various soil environments and tillage depths using a field load measurement system. A field load measurement system can measure the engine load, draft force, travel speed, wheel axle load, and tillage depth in real-time. In addition, measurement tests of soil properties in the soil layer were preceded to analyze the effect of field environments. The presented results show that moldboard plow at the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Other research produced similar findings; for various tillage implements, the OEE ranged from 11% to 20.08% [28]. Kim et al [47] assessed the range of draft force for a moldboard plow, finding that the overall mean draft force was 8.1 ± 1.4 kN (5.6-9.5 kN) in sandy loam soil, 10.1 ± 2.5 kN (6.4-13 kN) in loam soil, and 13.9 ± 2.5 kN (10.4-17.7 kN) in clay loam soil. Loam and clay loam soils displayed 1.24 and 1.71 times higher overall mean draft forces, respectively, than sandy loam.…”
Section: Statistical Data Analysismentioning
confidence: 55%
See 1 more Smart Citation
“…Other research produced similar findings; for various tillage implements, the OEE ranged from 11% to 20.08% [28]. Kim et al [47] assessed the range of draft force for a moldboard plow, finding that the overall mean draft force was 8.1 ± 1.4 kN (5.6-9.5 kN) in sandy loam soil, 10.1 ± 2.5 kN (6.4-13 kN) in loam soil, and 13.9 ± 2.5 kN (10.4-17.7 kN) in clay loam soil. Loam and clay loam soils displayed 1.24 and 1.71 times higher overall mean draft forces, respectively, than sandy loam.…”
Section: Statistical Data Analysismentioning
confidence: 55%
“…This is due to the fact that an increase in plowing speed leads to an increase in traction requirements; thus, the amount of fuel consumed based on traction power decreases. The soil texture index contributed by 4.07% to specific fuel consumption predictions; however, Kim et al [47] reported that draft forces were different and consequently so was fuel consumption.…”
Section: Contribution Analysis Of the Affecting Parameters On Predict...mentioning
confidence: 99%
“…The data obtained from previous studies were utilized to validate the regression models derived in this study [31]. The study evaluated the tractor's operational performance using the same tractor-moldboard plow combination.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al's (2022) model validation was performed using soil physical properties and LF data reported in [31]. The MAPE of the models varied between 5.19 and 12.55%, with models using multiple soil variables tending to have lower errors.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of tractor loading were mainly conducted based on the tillage force prediction and analysis. Tillage force is the force required to pull an implement in the direction of tractor operation and it is mainly affected by the driving speed (i.e., gear selection), machine geometry, tillage depth and soil environment (e.g., soil texture, soil properties, water content) [15]. The major objective of measurement results analysis was to evaluate the difference levels in draft force measured values within control limits in the experimental field between six representative adjacent passes.…”
Section: Introductionmentioning
confidence: 99%